2017
DOI: 10.1111/ans.14326
|View full text |Cite
|
Sign up to set email alerts
|

Cosmetic tourism for breast augmentation: a systematic review

Abstract: Determining the extent of cosmetic tourism for breast augmentation, including outcomes and complications, will help to inform Australian patients who this seek procedure abroad. Furthermore, it will aid in better understanding the health system implications and may help to guide future research and public health interventions both locally and internationally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 25 publications
2
12
0
1
Order By: Relevance
“…In response to the latest international consensus statement on Breast Implant Associated Anaplastic Large Cell Lymphoma, the Patient Safety Committee has disseminated practical guidelines for members, which is consistent with initiative 5. ICOPLAST will also look to build on the recent work by Brightman et al 7 entitled “Cosmetic tourism for breast augmentation: a systematic review,” which highlighted themes consistent with initiative 7.…”
Section: Discussionmentioning
confidence: 99%
“…In response to the latest international consensus statement on Breast Implant Associated Anaplastic Large Cell Lymphoma, the Patient Safety Committee has disseminated practical guidelines for members, which is consistent with initiative 5. ICOPLAST will also look to build on the recent work by Brightman et al 7 entitled “Cosmetic tourism for breast augmentation: a systematic review,” which highlighted themes consistent with initiative 7.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative complications may be immediate, such as LAST, or delayed up to months, as may occur with surgical site hematomas. 2,6 Figure 2 depicts common postoperative complications and clinical findings that may assist in distinguishing etiologies leading to ED presentation.…”
Section: Complications Of Cosmetic Surgical Proceduresmentioning
confidence: 99%
“…[2][3][4] Cosmetic procedures are lucrative, and in the absence of legal restrictions, are increasingly being performed in outpatient settings by non-plastic surgeons and even non-physicians. 5,6 Growing medical tourism has spurred demand for cosmetic surgery in Europe, South America, and Southeast Asia. [6][7][8] A survey distributed to 2000 active members of the American Society of Plastic Surgeons (ASPS) showed that 51.6% of respondents noted an increasing trend in the number of patients presenting with complications from surgical tourism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our efforts to improve the safety of patients with breast implants, 30% of whom are breast reconstruction cases for cancer or congenital deformities, we encourage all practitioners to ensure that their patients are registered with the ABDR so their implant details are securely stored 4 . In an effort to preserve the details of all Australian patients with breast implants, the ABDR can also store patient implant details retrospectively and will accept information from Australian patients having cosmetic tourism surgery overseas, after which significant complications can arise 5 . It may be time, however, for legislation to be enacted to lengthen the mandatory retention period for patients with high‐risk devices or to make it legally compulsory for practitioners inserting high‐risk devices to enrol all patients into a clinical quality registry such as the ABDR.…”
mentioning
confidence: 99%